Exploring the electromechanical response and electric field-induced dielectric anomalies in PMN-PT electroceramics - Guerra, J. D.S.; Guarany, C. A.; Lima, E. C.; Araújo, E. B. [UNESP]; Garcia, J. E. (World Scientific Publishing, 2021)
Electromechanical and dielectric properties of PMN-PT ferroelectric ceramics are investigated. In particular, dielectric response studies focus on the investigation of the influence of the DC applied electric field on the dielectric permittivity as a function of temperature and frequency. Results reveal an electric field driven dielectric anomaly in the dielectric permittivity curves, (E), which in turn prevails in the whole ferroelectric phase region and continuously vanishes for temperatures near the paraelectric-ferroelectric phase transition temperature. A schematic model for the domains dynamics of the studied material is proposed taking into account the simultaneous contribution of both 90° and 180° domains walls.
Keywords: dielectric response; domain-walls; electric field; Ferroelectrics; PMN-PT